Modified Learning Algorithm for GMDH-Wavelet-Neuro-Fuzzy-Network in Information Technologies - Vynokurova, O. (Індуктивне моделювання складних систем, 2013)
In the paper modified learning algorithm for GMDH-wavelet-neuro-fuzzy-network in information technologies is proposed. For Wavelet-Neuro-Fuzzy-Network structure optimization based on Group Method of Data Handling (GMDH) is developed and the method of structure optimization is described. Such hybrid systems can be used for solving many tasks including signal identification and prediction, person authentication, information classification and clustering, developing pseudo-random generator based on neural networks in cryptography and etc. The experimental investigations were carried out and their results accuracy of data processing by optimally constructed Wavelet-Neuro-Fuzzy-Network and network with multilayer feedforward architecture are presented and compared.